Translating EU AI Act Provisions into U.S. Enterprise Frameworks for Ethical and Responsible AI Use - Cyril Chimelie Anichukwueze; Vivian Chilee Osuji; Esther Ebunoluwa Oguntegbe (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The European Union Artificial Intelligence Act represents a landmark regulatory framework that establishes comprehensive standards for artificial intelligence governance, risk management, and ethical deployment across diverse sectors. As organizations worldwide grapple with the complexities of responsible AI implementation, the question of how to translate these European provisions into practical frameworks for American enterprise environments becomes increasingly critical. This research examines the systematic translation of EU AI Act provisions into actionable governance structures, compliance mechanisms, and operational protocols specifically tailored for U.S. enterprise contexts. Through comparative analysis of regulatory environments, stakeholder interviews, and organizational case studies, this study identifies key adaptation strategies that enable American corporations to leverage European AI governance principles while maintaining compatibility with domestic legal frameworks and business practices. The research methodology employs a mixed-methods approach combining regulatory analysis, expert consultation, and empirical evaluation of implementation strategies across multiple industry sectors including healthcare, financial services, manufacturing, and technology. Primary data collection involved structured interviews with 47 enterprise AI governance specialists, compliance officers, and legal practitioners representing organizations with annual revenues exceeding 1 billion. Secondary analysis incorporated extensive review of regulatory documentation, industry standards, and academic literature spanning 2018-2023 to establish comprehensive understanding of evolving AI governance landscapes. Key findings reveal that successful translation of EU AI Act provisions requires systematic adaptation across five critical dimensions: risk assessment methodologies, compliance monitoring systems, stakeholder engagement protocols, documentation requirements, and audit frameworks. Organizations demonstrating highest implementation success rates employed phased deployment strategies, comprehensive stakeholder training programs, and robust technological infrastructure supporting automated compliance monitoring. Notably, enterprises that proactively established cross-functional AI governance committees prior to formal implementation achieved 34% faster deployment timelines and 28% lower compliance-related operational costs compared to organizations adopting reactive approaches. The study identifies significant challenges in translating European regulatory concepts into American business contexts, particularly regarding cultural differences in risk tolerance, regulatory enforcement expectations, and organizational hierarchy structures. However, organizations successfully navigating these challenges developed innovative hybrid frameworks that preserved core ethical principles while accommodating domestic operational requirements. These frameworks demonstrated measurable improvements in AI system transparency, stakeholder trust, and long-term operational sustainability. Practical implications for enterprise leadership include the development of comprehensive AI governance roadmaps, investment in specialized compliance technologies, and establishment of cross-border regulatory monitoring capabilities. The research concludes that organizations implementing systematic translation frameworks achieve superior outcomes in ethical AI deployment, regulatory compliance, and stakeholder confidence compared to ad-hoc approaches. These findings contribute to the growing body of knowledge surrounding international AI governance harmonization and provide actionable guidance for enterprise practitioners navigating complex regulatory landscapes.